Negative emotions as predictors of blood pressure among hypertensive and normotensive residents of Gwarinpa: a community-based study in Abuja, Nigeria (2019)
The research was carried out to ascertain how negative emotions predict blood pressure among hypertensive and normotensive residents of Gwarinpa community. A cross-sectional ex-post-facto design was adopted for the study. A stratified random sampling technique was adopted in the selection process. Validated questionnaires were used to measure the six negative emotions, while a Sphygmomanometer was used to measure blood pressure. Binomial Logistic Regression Analysis was used to analyse the six hypotheses in the study. The result of the survey revealed that probability of being diagnosed of high blood pressure was more likely among participants with severe anxiety than participants with other levels anxiety (Exp (B) = 1.74, p <.01; 95% CI 0.60 – 0.92). The chance of being diagnosed of high blood pressure was significantly more likely among participants with severe psychological stress than participants with other levels of psychological stress (Exp (B) = 1.76, p <.001; 95% CI 1.66 – 1.891). The probability of being diagnosed of high blood pressure was significantly more likely among participants with emotional instability than participants with emotional stability (Exp (B) = 1.69, p <.001; 95% CI = 1.45 – 1.96). Findings further revealed that a unit increase in respondents’ level of dispositional optimism, significantly decreases the probabilities of being hypertensive (Exp (B) = -.40, p <.05; 95% CI 0.49 - 0.74). The study, therefore, concluded that severe anxiety, stress, emotional instability and high dispositional optimism were high-risk factors to high-blood pressure, while depression and life satisfaction are not necessarily risked factors for high blood pressure, while among the residents of Gwarinpa